Carbon derived from soft pyrolysis of a covalent organic framework as a support for small-sized RuO2 showing exceptionally low overpotential for oxygen evolution reaction - Chakraborty, Debanjan; Nandi, Shyamapada; Illathvalappil, Rajith; Mullangi, Dinesh; Maity, Rahul; Singh, Santosh K.; Haldar, Sattwick; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (ACS Omega, 2019)
Electrochemical water splitting is the most energy-efficient technique for producing hydrogen and oxygen, the two valuable gases. However, it is limited by the slow kinetics of the anodic oxygen evolution reaction (OER), which can be improved using catalysts. Covalent organic framework (COF)-derived porous carbon can serve as an excellent catalyst support. Here, we report high electrocatalytic activity of two composites, formed by supporting RuO2 on carbon derived from two COFs with closely related structures. These composites catalyze oxygen evolution from alkaline media with overpotentials as low as 210 and 217 mV at 10 mA/cm(2), respectively. The Tafel slopes of these catalysts (65 and 67 mV/dec) indicate fast kinetics compared to commercial RuO2. The observed activity is the highest among all RuO2-based heterogeneous OER catalysts-a touted benchmark OER catalyst. The high catalytic activity arises from the extremely small-sized (similar to 3-4 nm) RuO2 nanoparticles homogeneously dispersed in a micro-mesoporous (BET = 517 m(2)/g) COF-derived carbon. The porous graphenic carbon favors mass transfer, while its N-rich framework anchors the catalytic nanoparticles, making it highly stable and recyclable. Crucially, the soft pyrolysis of the COF enables the formation of porous carbon and simultaneous growth of small RuO2 particles without aggregation.

Cu/Cu2O nanoparticles supported on a phenol-pyridyl COF as a heterogeneous catalyst for the synthesis of unsymmetrical diynes via glaser-hay coupling - Chakraborty, Debanjan; Nandi, Shyamapada; Mullangi, Dinesh; Haldar, Sattwick; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (ACS Applied Materials & Interfaces, 2019)
Covalent organic frameworks (COFs) are a new class of porous crystalline polymers with a modular construct that favors fiinctionalization. COF pores can be used to grow nanoparticles (nPs) with dramatic size reduction, stabilize them as dispersions, and provide excellent nP access. Embedding substrate binding sites in COFs can generate host-guest synergy, leading to enhanced catalytic activity. In this report, Cu/Cu2O nPs (2-3 nm) are grown on a COF, which is built by linking a phenolic trialdehyde and a triamine through Schiff bonds. Their micropores restrict the nP to exceptionally small sizes (similar to 2-3 nm), and the pore walls decorated with strategically positioned hydrogen-bonding phenolic groups anchor the substrates via hydrogen-bonding, whereas the basic pyridyl sites serve as cationic species to stabilize the [CuclusterCl2](2-) type reactive intermediates. This composite catalyst shows high activity for Glaser-Hay heterocoupling reactions, an essential 1,3-diyne yielding reaction with widespread applicability in organic synthesis and material science. Despite their broad successes in homocoupled products, preparation of unsymmetrical 1,3-diynes is challenging due to poor selectivity. Here, our COF-based Cu catalyst shows elevated selectivity toward heterocoupling product(s) (Cu nP loading 0.0992 mol %; turn over frequency: similar to 4S-50; turn over number: similar to 17S-190). The reversible redox activity at the Cu centers has been demonstrated by carrying out X-ray photoelectron spectroscopy on the frozen reactions, whereas the crucial interactions between the substrates and the binding sites in their optimized configurations have been modeled using density functional theory methods. This report emphasizes the utility of COFs in developing a heterogeneous catalyst for a truly challenging organic heterocoupling reaction.
Keywords: Copper nanoparticles; Covalent organic framework; Glaser-Hay heterocoupling; heterogeneous catalysis; unsymmetrical diynes

Can we identify the salt-cocrystal continuum state using XPS? - Tothadi, Srinu; Shaikh, Tabrez Rafique; Gupta, Sharad; Dandela, Rambabu; Vinod, Chathakudath P.; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
X-ray photoelectron spectroscopy (XPS) is used to understand the nature of acid-base crystalline solids, to know whether the product is a salt (proton transfer, O-center dot center dot center dot H-N+) or a cocrystal (neutral adduct, O-H center dot center dot center dot N). The present study was carried out to explore if intermediate states of proton transfer from COOH to nitrogen (the proton resides between hydrogen bonded to O and N, O center dot center dot center dot H center dot center dot center dot N, quasi state) can be differentiated from a salt (complete proton transfer, N+-H center dot center dot center dot center dot O-) and cocrystal (no proton transfer, O-H center dot center dot center dot N) using N 1s XPS spectroscopy. The intermediate states of proton transfer arise when the pK(a) difference between the acid and the conjugate base is between -1 and 4, -1 < Delta pK(a) < 4, a situation common with COOH and pyridine functional groups present in drug molecules and pharmaceutically acceptable coformers. Complexes of pyridine N bases with aromatic COOH molecules in nine salts/cocrystals were cocrystallized, and their N 1s core binding energies in XPS spectra were measured. The proton state was analyzed by single-crystal X-ray diffraction for confirmation. Three new complexes were crystallized and analyzed by XPS spectra (without knowledge of their X-ray structures), to assess the predictive ability of XPS spectra in differentiating salt-cocrystal intermediate states against the extremities. The XPS results were subsequently confirmed by single-crystal X-ray data. Complexes of 3,5-dinitrobenzoic acid and isonicotinamide in 1:1 and 1:2 ratios exist as a salt and a salt-cocrystal continuum, respectively, as shown by the N 1s core binding energies. The proton states of the crystalline solids by XPS are in good agreement with the corresponding crystal structures. Other complexes, such as those of 3,5-dinitrobenzoic acid with 1,2-bis(4-pyridyl)ethylene, exhibit a salt-cocrystal continuum, maleic acids with 1,2-bis(4-pyridyl)ethylene and acridine are salts, 2-hydroxybenzoic acid and acridine is a salt, and the complex of 3,5-dinitrobenzoic acid and 3-hydroxypyridine is a salt and salt-cocrystal continuum, while fumaric acids with 1,2-bis(4-pyridyl)ethylene and acridine are cocrystals. Furthermore, three new acidbase complexes of 3,5-dinitrobenzoic acid with phenazine, 4-hydroxypyridine, and 4-cyanopyridine were studied initially by XPS and then confirmed by X-ray diffraction. In summary, since the N 1s binding energies cluster in a narrow range as cocrystals (398.7-398.9 eV) and salts (400.1-401.1 eV), it is clearly possible to differentiate between cocrystals and salts, but the saltcocrystal continuum values in XPS spectra are clustered in an intermediate range of cocrystals and salts but overlap with those of cocrystal or salt binding energies.

Coordination flexibility aided CO2-specific gating in an iron isonicotinate MOF - Singh, Himan Dev; Nandi, Shyamapada; Chakraborty, Debanjan; Singh, Kirandeep; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Chemistry-an Asian Journal, 2022)
Coordination flexibility assisted porosity has been introduced into an Iron-isonicotinate metal-organic framework (MOF), (Fe(4-PyC)(2) . (OH). The framework showed CO2-specific gate opening behavior, which gets tuned as a function of temperature and pressure. The MOF ` s physisorptive porosity towards CO2, CH4, and N-2 was investigated; it adsorbed only CO2 via a gate opening phenomenon. The isonicotinate, representing a borderline soft base, is bound to the hard Fe3+ centre through monodentate carboxylate and pyridyl nitrogen. This moderately weak binding enables isonicotinate to spin like a spindle under the CO2 pressure opening the gate for a sharp increase in CO2 uptake at 333 mmHg (At 298 K, the CO2 uptake increases from 0.70 to 1.57 mmol/g). We investigated the MOF ` s potential for CO2/N-2 and CO2/CH4 gas separation aided by this gating. IAST model reveals that the CO2/N-2 selectivity jumps from 325 to 3131 when the gate opens, while the CO2/CH4 selectivity increases three times. Interestingly, this Fe-isonicotinate MOF did not follow the trend set by our earlier reported Hard-Soft Gate Control (established for isostructural M2+-isonicotinate MOFs (M=Mg, Mn)). However, we account for this discrepancy using the different oxidation state of metals confirmed by X-ray photoelectron spectroscopy and magnetism.
Keywords: CO2 capture; flexible MOF; gating; Isonicotinic

Covalent organic framework with electrodeposited copper nanoparticles - a desirable catalyst for the Ullmann coupling reaction - Chandran, Chandana; Singh, Himan Dev; Leo, Liya S.; Shekhar, Pragalbh; Rase, Deepak; Chakraborty, Debanjan; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Journal of Materials Chemistry A, 2022)
A covalent organic framework is a porous covalently-linked polymeric assembly built from molecular lego blocks, the monomers. A COF's high surface area, ordered pores, and intrinsic low density makes it a perfect heterogeneous catalyst component. Dispersing catalytic metal nanoparticles into the porous COF matrix in a `capping-agent-free' manner can aid the maximal utilization of the active sites. To generate single-site catalysts, metals have been anchored to dense supports, or metal ions have been coordinated to the porous organic framework. The latter has superior atom efficiency and a substrate diffusion advantage. Stably nestling neutral metallic clusters into open-framework supports with no specifically strong binding groups requires a different approach. If infused from extremely dilute electrolytes, metal clusters can be nanoconfined into electrically activated COFs. At low-loadings, it can resemble a single-site catalyst with high atom efficiency. Herein, we report the larger scale synthesis of IISERP-COF15 and electrochemical loading of copper nanoparticles into its pores at loadings as low as 3.34 wt%. We employed classical Ullmann reactions to adjudge its activity. Typical turnover numbers for the catalysts reported in the literature are approximately 50-100. A Cu@COF shows high activity with a very low catalyst loading of 0.25 mol% (TON around similar to 300-350 vs. 4 for neat CuCl2 center dot 2H(2)O (homogeneous catalyst) and turnover frequency (similar to 15-17 h(-1))). We recycled it for up to 3 cycles. Furthermore, we report a multi-fold Ullmann reaction producing an unreported hexaaldehyde to demonstrate the latitude of the catalyst. Our work points to the potential of a dilutely loaded metal@COF as a mimic of the single-site catalyst for synthesizing valuable C-O linked molecules. Our findings from computational modeling shed light on the role of the COF as an active nanoporous support for Ullmann C-O coupling.